Akibat Hukum Dari Perkawinan Polandri Di Pengadilan Agama Gorontalo - Siti Nur Magfirah A. Hudodo; Nur Mohamad Kasim; Sri Nanang Meiske Kamba (Deposisi: Jurnal Publikasi Ilmu Hukum, 2023)
This research aims to find out the juridical perspective on polyandrous marriages and what the legal consequences of polyandrous marriages are in the Gorontalo Religious Court. This research uses normative legal research methods or normative juridical research. This normative research includes library research or document study, because the objects studied are official public documents, namely official data from the Gorontalo Religious Court. Legal research carried out by examining library materials or secondary data alone can be called normative legal research or library legal research supported by empirical data. The results of this research show that the legal consequences of polyandrous marriages in the Gorontalo Religious Court are that the biggest difficulty in polyandry is that the father of the child is not known, so that in this model of marriage the relationship between father and child is uncertain. Just as sexual communism has no foothold, so polyandry cannot be popular in any society. Therefore, family life which is a safe building of protection for the next generation and a strict connection between one generation and the next is an instinctive demand of human nature.